Estimating marginal returns to education - Pedro Carneiro; James Heckman; Edward Vytlacil (Centre for Microdata Methods and Practice (cemmap), 2010)
This paper estimates the marginal returns to college for individuals induced to enroll in college by different marginal policy changes. The recent instrumental variables literature seeks to estimate this parameter, but in general it does so only under strong assumptions that are tested and found wanting. We show how to utilize economic theory and local instrumental variables estimators to estimate the effect of marginal policy changes. Our empirical analysis shows that returns are higher for individuals more likely to attend college. We contrast the returns to well-defined marginal policy changes with IV estimates of the return to schooling. Some marginal policy changes inducing students into college produce very low returns.
Keywords: J31; 330; Returns to Schooling; Marginal Return; Average Return; Marginal Treatment Effect; Bildungswesen; Bildungspolitik; Politische Reform; Bildungsertrag; USA